Albumin/fibrinogen ratio (AFR): a significant predictor of postoperative delirium in older patients undergoing non-neurosurgical and non-cardiac surgery - Jiang Huo; Yuxiang Song; Jing Lu; Guijin Dou; Huixian Chen; Weidong Mi; Yingqun Yu; Yanhong Liu (BMC Geriatrics)
Abstract Objective The purpose of this research was to evaluate the prognostic significance of preoperative albumin to fibrinogen (AFR) for postoperative delirium (POD) in older patients with non-neurosurgical and non-cardiac surgery. Method The retrospective cohort study included a group of patients aged 65 and above who underwent non-neurosurgical and non-cardiac surgery at the First Medical Center of Chinese PLA General Hospital from January 2014 to December 2021. AFR and POD correlation was evaluated through univariate and multivariable logistic regression analysis, as well as propensity score matching (PSM) and subgroup analysis. Results In our study, the occurrence of POD was 2.9% (1566/53,609), with the AFR threshold identified as 10.625 based on the ROC curve. The study identified AFR ≤ 10.625 as a significant predictor of POD in both univariate and multivariable regression analyses, and the odds ratios (OR) were 2.65 (2.40–2.93), 1.98 (1.79–2.21), 1.51 (1.34–1.70), 1.27 (1.13–1.43) and 1.32 (1.14–1.53) in four models and the PSM model. Conclusion AFR is a valuable predictor for predicting the development of POD in older patients receiving non-neurosurgical and non-cardiac procedures. This finding highlights the importance of preoperative assessment of AFR in these patients to better predict and manage the risk of POD.